Biallelic SEMA3A defects cause a novel type of syndromic short stature. Issue 11 (3rd October 2013) - Hofmann, Kristin; Zweier, Markus; Sticht, Heinrich; Zweier, Christiane; Wittmann, Wolfgang; Hoyer, Juliane; Uebe, Steffen; van Haeringen, Arie; Thiel, Christian T.; Ekici, Arif B.; Reis, André; Rauch, Anita
ABSTRACT Chromosomal microarray testing is commonly used to identify disease causing de novo copy number variants in patients with developmental delay and multiple congenital anomalies. In such a patient we now observed an 150 kb deletion on chromosome 7q21.11 affecting the first exon of the axon guidance molecule gene SEMA3A (sema domain, immunoglobulin domain (Ig), short basic domain, secreted, (semaphorin) 3A). This deletion was inherited from the healthy father, but considering the function of SEMA3A and phenotypic similarity to the knock‐out mice, we still assumed a pathogenic relevance and tested for a recessive second defect. Sequencing of SEMA3A in the patient indeed revealed the de novo in‐frame mutation p.Phe316_Lys317delinsThrSerSerAsnGlu. Cloning of the mutated allele in combination with two informative SNPs confirmed compound heterozygosity in the patient. While the altered protein structure was predicted to be benign, aberrant splicing resulting in a premature stop codon was proven by RT‐PCR to occur in about half of the transcripts from this allele. Expression profiling in human fetal and adult cDNA panels, confirmed a high expression of SEMA3A in all brain regions as well as in adult and fetal heart and fetal skeletal muscle. Normal intellectual development in the patient was surprising but may be explained by the remaining 20% of SEMA3A expression level demonstrated by quantitative RT‐PCR. We therefore report a novel autosomal recessive syndrome characterized by postnatal short stature with relative macrocephaly, camptodactyly, septal heart defect and several minor anomalies caused by biallelic mutations in SEMA3A. © 2013 Wiley Periodicals, Inc.